OPTIMALISASI PENGGUNAAN P4K SEBAGAI UPAYA PENINGKATAN PENCEGAHAN KOMPLIKASI PERSALINAN OLEH KADER - Ria Verti Sandika Arif; Dian Permatasari; Eko Mulyadi (STAI Nurul Huda Kapongan Situbondo, 2026)
The maternal mortality rate in Indonesia remains relatively high. One contributing factor is the low level of knowledge among pregnant women and their families regarding recognizing pregnancy danger signs and preparing for Potential adverse outcomes. The Childbirth Planning and Complication Prevention (P4K) program is a government initiative designed to lower maternal mortality by empowering communities, especially health cadres. This community service initiative seeks to enhance the knowledge and capabilities of integrated health post cadres in implementing P4K through participatory educational approaches. The activity was carried out at the Posyandu within the Jrangoan Community Health Center working area and involved 25 participants. Based on the pre-test and post-test findings, there was an improvement in the cadres' knowledge regarding the importance of educational activities. Before the education, 40% of respondents were in the poor category, while after the education, this figure increased to 20%. There were 28% of respondents before the education, and after the education, this figure increased to 44%. These results demonstrate that educational interventions effectively support the successful implementation of the P4K program at the community level. Continuous active involvement of participants and the provision of adequate resources, especially for cadres, can encourage the creation of a more informative and proactive approach in efforts to improve maternal and child health. Therefore, strengthening the role of cadres is an important factor in preventing childbirth complications.